Pengaruh Rekrutment Pegawai, Pelatihan Karyawan Terhadap Kinerja Karyawan Pada UKM (Studi Kasus Rumah Makan Kebun Pondok Punokawan, Binjai) - Merry Moy Mita (Universitas 17 Agustus 1945, 2022)
The process of finding employees, or what is often called employee recruitment, is an important concern for employers. Recruitment is carried out with the hope of getting employees with the required classification. After the recruitment process is carried out, it is necessary to conduct training for new employees according to their job title. The training was conducted to equip employees to be more creative and able to provide excellent service to visitors. Training is one of the efforts to achieve the service standards that have been set in the business. The population and sample of this study were all 37 employees at RIC, with the data collection method in this study being a questionnaire that will be distributed to employees. The list of questions on the research questionnaire uses a Likert scale. The data analysis method uses descriptive qualitative analysis, namely by distributing questionnaires to respondents to solve the problems to be studied, and quantitative analysis is carried out by processing the data using the SPSS version 23 software tool. From the results of the study, it can be concluded that there is a significant influence between recruitment and training on employee performance at Coffee Idea House. This means that business people must pay attention to a good recruitment process and intense training to improve employee performance.